QUALITY MANAGEMENT: IMPACT OF LEADERSHIP MOBILIZATION ON INSTITUTIONAL QUALITY - Linda Septarina & Rambat Nur Sasongko (International Journal of Research Science and Management, 2019)
The quality of institutions is very dependent on the performance of leaders in mobilizing subordinates. Allegedly, leaders who lack mobilize quality management have a negative impact on the quality of institutions. This study purposes to analyze the impact of leadership mobilization in implementing quality management on quality in educational institutions, in this case the school. The study uses descriptive methods. The research approach is descriptive correlational. The research was conducted at various levels of schools (elementary schools, junior high schools, senior high school and vocational high schools) in Bengkulu province, Indonesia. The results of the study show that leaders who carry out high mobility towards quality management will have a positive impact on improving the quality of institutions. The quality of educational institutions analyzed in terms of the application of national education standards, the value of school accreditation, and the average school / national examination scores, shows a positive impact. Mobilization of leaders who have low levels has a negative impact on the achievement of institutional quality. Recommendations to authority holders, policy makers, and leaders to improve skills in mobilizing quality management, through various activities such as training, mentoring, practice simulation on a small scale, and lesson study on human resource mobilization